Mechanism of cement/carbon nanotube composites with enhanced mechanical properties achieved by interfacial strengthening. (15th July 2016) - Sun, Guoxing; Liang, Rui; Lu, Zeyu; Zhang, Jinrui; Li, Zongjin
Highlights: Carbon nanotubes disperse in cement paste with polyvinyl alcohol as bridging agent. The interaction among cement, PVA, and acid-treated carbon nanotube is studied. Flexural strength of cement/polyvinyl alcohol/carbon nanotube is enhanced. The enhancement is also found in cement/polyvinyl alcohol/graphene oxide composite. Abstract: The mixing of carbon nanotubes (CNTs) with cement or concrete to form cementitious composites has been practiced for decades. CNTs usually aggregate, and have very weak interfacial interaction with the cement matrix, which negates any benefits associated with the original properties of the CNTs. In this study, we present a novel method for interfacial enhancement between surface-treated CNTs and the cement matrix using polyvinyl alcohol (PVA) as the bridging agent. Compared with the slight enhancement effect of untreated CNTs, the flexural strength of cementitious composites containing 0.05 wt% surface-treated CNTs increased from 5.52 to 12.61 MPa with the interfacial strengthening of PVA. A similar flexural strengthening was also found by using graphene oxide (GO) to replace CNTs. Our findings demonstrate that the flexural strength of cement/CNT (or GO) composites can be clearly increased by interfacial strengthening between the CNTs (or GO) and the cement matrix.